Alaskan Holiday : Novel - Macomber, Debbie (New York Ballantine Books, 2018)
"Before beginning her new job as sous chef at one of Seattle's finest restaurants, Josie Stewart takes on a six-month position cooking at a lodge in an Alaskan lake town. It's only temporary--or so she thinks, as she becomes a valued part of the local community, falling in love with the people who call Klutina Lake home. But one Alaskan man, in particular, stands out among Josie's new friends: Palmer Saxon, a quiet, intense sword craftsman, whose very existence forces her to question whether her heart wants to return to Washington at all--or make Alaska her home"--
Keywords: Women cooks -- Fiction; Interpersonal attraction -- Fiction; Man-woman relationships -- Fiction -- Alaska; Christmas stories; FICTION / Romance / Contemporary; FICTION / Contemporary Women; Alaska -- Fiction; Romance fiction; Christmas fiction